2007
DOI: 10.1038/sj.jhh.1002153
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood pressure reactivity to dietary salt in patients with the metabolic syndrome

Abstract: The metabolic syndrome is a predictor of type II diabetes mellitus and cardiovascular disease. The mechanisms of the increased blood pressure (BP) in patients with the metabolic syndrome are poorly understood. We investigated if salt-sensitivity is a characteristic of the metabolic syndrome. A total of 301 subjects (87male subjects, 214 female subjects) of 41.570.7 years of age completed a salt sensitivity test, and were evaluated for the presence of metabolic syndrome. BP and 24-h sodium excretion were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…High blood pressure, as a component of MS, is largely related to dietary salt [36,37]. The enhanced blood pressure reactivity to dietary salt observed in subjects with MS, may determine the increased blood pressure levels commonly associated with the syndrome [36]. The results from our study showed that nutrition habit to add salt to meals at the table almost always significantly increased the risk of arterial hypertension in women aged 50-64 years.…”
Section: Data Adjusted For Age Education and All Listed Lifestyle Fasupporting
confidence: 66%
See 1 more Smart Citation
“…High blood pressure, as a component of MS, is largely related to dietary salt [36,37]. The enhanced blood pressure reactivity to dietary salt observed in subjects with MS, may determine the increased blood pressure levels commonly associated with the syndrome [36]. The results from our study showed that nutrition habit to add salt to meals at the table almost always significantly increased the risk of arterial hypertension in women aged 50-64 years.…”
Section: Data Adjusted For Age Education and All Listed Lifestyle Fasupporting
confidence: 66%
“…Analysis according to food categories in Australian women with PMS showed a significant greater intake in fat, and all macronutrients for cereals, cakes and desserts and high-sugar foods [35]. High blood pressure, as a component of MS, is largely related to dietary salt [36,37]. The enhanced blood pressure reactivity to dietary salt observed in subjects with MS, may determine the increased blood pressure levels commonly associated with the syndrome [36].…”
Section: Data Adjusted For Age Education and All Listed Lifestyle Famentioning
confidence: 99%
“…Salt-induced BP hyperreactivity or renal injury has been reported in MetS patients or in MetS animal models. 8,9 In the present study, LV diastolic function was apparently impaired when salt was loaded in SHR/cps. Therefore, excess salt may play a pivotal role in the progression of organ damage in MetS.…”
Section: Discussionmentioning
confidence: 75%
“…In patients with MetS, high salt intake increased blood pressure (BP) greater than in those without MetS. 8 In an MetS rat model, evident renal injury was induced by salt loading. 9 These findings suggest that the MetS model is highly susceptible to salt-induced organ damage.…”
mentioning
confidence: 99%
“…A decrease in sodium intake could be used to modulate blood pressure in MS due to a significant reduction in arterial blood pressure was detected with a low sodium ingestion. Supplementary, another study 52 Another previous study 59 examined the protein content in obese participants for 12 months. They were assigned to a high protein diet (1.34 g per kg of BM) or to a standard protein diet (0.8 g per kg of BM) and a calorie restriction of 500 kcal per day.…”
Section: Nutritional Treatments Proposedmentioning
confidence: 99%